2014
DOI: 10.1080/01496395.2013.871560
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Modeling and Experimental Study of Crude Oil Desalting using Microwave

Abstract: In this study a novel experimental procedure for the crude oil desalting process using microwave field is designed and a mathematical model is developed to predict the global coalescence rates and the evolution of the saltwater separation under the influence of the microwave field. The results of the model are validated by experimental data and a good qualitative agreement between the model predictions and experimental results is observed. Using the model, the effects of microwave residence time, volumetric en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…10 reveals that the percentage of water separated from the crude oil sample 030 (high salt), is slightly higher than for the crude oil sample 020. This trend is similar to that observed in microwave experiments that have also shown that the segregation of emulsion water droplets from crude oil occurs more readily if the crude oil’s salt content is higher [65] .…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…10 reveals that the percentage of water separated from the crude oil sample 030 (high salt), is slightly higher than for the crude oil sample 020. This trend is similar to that observed in microwave experiments that have also shown that the segregation of emulsion water droplets from crude oil occurs more readily if the crude oil’s salt content is higher [65] .…”
Section: Resultssupporting
confidence: 87%
“…This model assumes that the water droplets in crude oil are dependent upon and related to an empirically-derived function β related to adhesion coefficients. Previously published studies on crude oil samples have applied a drop-pair model to assess the displacement of water droplets in crude oil samples tested with microwave and ultrasonic irradiation [65] . In those experiments, the irradiation time in the microwave chamber was 15 s [66] , while in the experiments conducted for this study the ultrasonic irradiation time was between 1 and 5 min.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The advantages of microwave heating technology help it to be applied as a standalone pathway for demulsification of emulsions in petroleum industry, by eliminating or minimizing the consumption of chemical demulsifiers [242,243]. Microwaves generate electromagnetic waves with wavelength range of 1 mm to 100 cm and frequencies between 300 GHz and 300 MHz, enabling them to deliver far higher reaction productivities than traditional heating methods at a specific temperature or even at lower temperatures in a variety of applications, including inorganic or organic synthesis, food processing, environmental chemistry, analytical chemistry, and polymerization [238,244].…”
Section: Microwave Irradiationmentioning
confidence: 99%